The impact of nurse staffing on turnover and quality: An empirical examination of nursing care within hospital units - Peng, Xiaosong (David); Ye, Yuan; Ding, Xin (David); Chandrasekaran, Aravind (Journal of Operations Management, 2023)
AbstractInadequate nurse staffing continues to challenge healthcare delivery in the United States. In this research, we undertake a fine‐grained, unit‐level analysis to understand the relationships between nurse staffing, nurse turnover, and pressure ulcers, the latter of which is a key nursing‐sensitive care quality indicator. We examine these relationships within two types of hospital units: intensive care units (ICUs) and medical‐surgical (MedSurg) units, which have unique patient mixes and needs. Using hospital unit‐level data between 2008 and 2017, we show that nurse staffing primarily affects nurse turnover in ICUs, and that the adverse effects of nurse turnover on care quality tend to be stronger in ICUs than in MedSurg units. These findings provide important theoretical insights into the varying roles of staffing, turnover, and quality across organizational units. The findings suggest that hospital administrators may prioritize staffing needs for ICUs over MedSurg units to maintain strong quality performance on measures such as pressure ulcers. Further, our study reveals that staffing requirements for ICUs may be inadequate compared with MedSurg units. Thus, there is a need to evaluate existing guidelines on ICU staffing.